Excitability of spinal motor neurons during motor imagery of thenar muscle activity under maximal voluntary contractions of 50% and 100% - Bunno, Yoshibumi (J Phys Ther Sci, 2015)
[Purpose] We often perform physical therapy using motor imagery of muscle contraction to improve motor function for healthy subjects and central nerve disorders. This study aimed to determine the differences in the excitability of spinal motor neurons during motor imagery of a muscle contraction at different contraction strengths. [Subjects] We recorded the F-wave in 15 healthy subjects. [Methods] In resting trial, the muscle was relaxed during F-wave recording. For motor imagery trial, subjects were instructed to imagine maximal voluntary contractions of 50% and 100% while holding the sensor of a pinch meter, and F-waves were recorded for each contraction. The F-wave was recorded immediately after motor imagery. [Results] Persistence and F/M amplitude ratio during motor imagery under maximal voluntary contractions of 50% and 100% were significantly higher than that at rest. In addition, the relative values of persistence, F/M amplitude ratio, and latency were similar during motor imagery under the two muscle contraction strengths. [Conclusion] Motor imagery under maximal voluntary contractions of 50% and 100% can increase the excitability of spinal motor neurons. Differences in the imagined muscle contraction strengths are not involved in changes in the excitability of spinal motor neurons.